Kajian Pada Ramp Sebagai Elemen Aksesibilitas Pada Bangunan Pelayanan Publik Di Jakarta (Kasus Studi: 17 Kantor Kelurahan Di Jakarta Barat) - adli nadia; Della Clarissa (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2023)
Ramps as part of the inclusion design have been implemented in various spaces and public service buildings in Jakarta. In addition to facilitating accessibility for persons with disabilities, ramps also play a role in building a sense of equality in the social aspects of society. However, even though ramps have been attempted to be present in most public service buildings, the quality and consistency of the application of laws and regulations and the perception of equality among users have never been studied further. This research will involve 17 Kelurahan offices in West Jakarta and will be measured by 10 design criteria from PERMEN no 30/PRT/M/2006 Technical Guidelines for Facilities and Accessibility in Buildings and the Environment. Research method applied in this study involved direct observation and empirical measurement and involved 5 people with disabilities to build a narrative perception of equality. This study aims to reveal the actual condition of the ramp in Kelurahan offices and the consistency of its application to SNI. In addition, this study also aims to explain the importance of involving communities with disabilities in the planning, monitoring and evaluation phases of ramps as a means of accessibility in public service buildings in the future.